Digitalisasi proses gadai emas syariah dan dampaknya terhadap efisiensi layanan: Studi pada Bank Syariah Indonesia (BSI) - Audyzza, Keysa Fahradine (Maliki Interdisciplinary Journal, 2026)
The digitalization of sharia-compliant gold pawn services has brought about fundamental changes in the operational mechanisms and service quality at Bank Syariah Indonesia (BSI). This transformation has simplified transaction flows, increased recording accuracy, and accelerated administrative processes through the integration of digital applications. Customers can now access a variety of services in real time, from fee simulations and pawn status monitoring to tenor extensions, significantly increasing efficiency and convenience. At the same time, digitalization has expanded financial inclusion by providing more equitable access to services. However, given that gold pawning involves physical assets, digitalization cannot completely eliminate the need for manual verification and appraisal processes at branch offices. Additional challenges arise from sharia compliance, data security, and the digital literacy gap among users. Therefore, strengthening governance, sharia validation, and implementing digital security systems are essential to ensure that service quality remains compliant with sharia principles. Overall, the digitalization of gold pawning at BSI has the potential to strengthen the competitiveness of Islamic banks in the digital economy era, with the caveat that implementation must be carried out carefully, comprehensively, and oriented towards risk mitigation.